Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
The correct statements are B and D.
Step-by-step explanation:
The equation [tex](x-3)^2+(y+1)^2=9[/tex] reminds us of the circle equation [tex]\boxed{(x-a)^2+(y-b)^2=r^2}[/tex], where:
- [tex](a,b)[/tex] = coordinate of the circle's center
- [tex]r[/tex] = radius
In order to find the center and the radius, we convert the equation into the standard form:
[tex](x-3)^2+(y+1)^2=9[/tex]
[tex](x-(3))^2+(y-(-1))^2=3^2[/tex]
Therefore:
- center [tex](a,b)[/tex] = (3, -1)
- radius ([tex]r[/tex]) = 3
Hence, options A and C are incorrect and option B is correct.
for option D:
When the equation intersects the x-axis, the y-value = 0.
[tex](x-3)^2+(y+1)^2=9[/tex] → substitute [tex]y[/tex] with 0
[tex](x-3)^2+(0+1)^2=9[/tex]
[tex](x-3)^2=9-1[/tex]
[tex]x-3=\pm\sqrt{8}[/tex]
[tex]x=\pm2\sqrt{2} +3[/tex]
[tex]x=2\sqrt{2} +3\ or\ -2\sqrt{2} +3[/tex]
Since there are 2 solutions for x-value, then the equations intersects the x-axis twice. (option D is correct)
for option E:
When the equation intersects the y-axis, the x-value = 0.
[tex](x-3)^2+(y+1)^2=9[/tex] → substitute [tex]x[/tex] with 0
[tex](0-3)^2+(y+1)^2=9[/tex]
[tex](y+1)^2=9-9[/tex]
[tex]y+1=0[/tex]
[tex]y=-1[/tex]
Since there is only 1 solution for y-value, then the equations tangent to the y-axis. (option E is incorrect)
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.